Фізичне виховання дівчат у гімназіях Тернопільського воєводства міжвоєнного періоду - Гук, О.; Huk, A. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
У статті розглянуто проблему фізичного виховання дівчат у гімназіях Тернопілля в період між Першою й Другою світовими війнами, де питання становлення фізично розвинутої, спортивної молоді було одним із головних. За допомогою використання матеріалів наукових праць та архівних даних проаналізовано форми та засоби фізичного виховання дівчат-гімназисток. Розкрито тему особистої гігієни учениць та ведення ними відповідних щоденників, що сприяло дотриманню дисципліни та здоровому способу життя. Висвітлено діяльність учителів фізичного виховання та опікунів гімназій, які залучали учениць до позакласних заходів, до участі в руханкових товариствах та спортивних святах. Розкрито участь дівчат у спортивних гуртках і секціях, що сприяли фізичному вихованню учениць гімназій. . The article deals with the physical education of girls at the gymnasiums in Ternopil province during the period between the First and Second World Wars, where the problem of upbringing physically-developed and sports trained youth was one of the dominant ones. The analysis of forms and means of physical education of schoolgirls has been done due to the usage of materials from the relevant scientific publications and archival data. The article reveals the topic of schoolgirls’ personal hygiene and keeping special hygiene diaries, which contributed to the discipline and a healthy lifestyle observance. The physical training teachers’ and guardians’ work has been investigated; they encouraged the schoolgirls’ extracurricular activities and promoted their participation in gymnastic societies as well as sports events at the gymnasiums. The girls’ participation in sports clubs, which facilitated girls physical upbringing, is being revealed.
The Physical Education of Girls at the Gymnasiums in Ternopil Province During the Interwar Period
Keywords: гімназія; руханка; спортивні гуртки; дівочий (жіночий) спорт; gymnasium; gymnastics; sports clubs; girls (women) sport.